Strategi komunikasi kanak-kanak Jepun prasekolah / Azni Ahmad - Azni, Ahmad (2012)
This study was conducted with the objective to see the communication strategies used by Japanese preschool children during play. In addition, this study will also discuss the values of harmony in the communication strategies detected. The respondents were children from aged between 3 to 6 years old who were enrolled in a Japanese preschool in Kuala Lumpur. Naturalistic observation is applied as an instrument to collect data. While the data was transcribed, then analysed by using Corsaro (1986) Communication Model as guideline. The findings have identified questions, call, protest, demand and repetition as strategies used by the respondents. In addition, elements such as empathy, cooperation and responsibility were detected as the harmony values shown during the interaction Thus, the study will help to increase the knowledge of the Malaysian society about Japanese preschool children’s communication strategies that occurs in their socialization process.